The awareness and practices customers’ preference on Islamic vehicle financing among staff in UiTM Puncak Alam / Siti Nur Aqilah Suhaimi - Suhaimi, Siti Nur Aqilah (Academy of Contemporary Islamic Studies (ACIS), 2018)
In Malaysia, there are many product financing in banking institution that was provided vehicle product whether Islamic or conventional banking. The aim of this study is to know the level of customer understanding and awareness on Islamic vehicle financing, thus it will affect their selection on Islamic vehicle financing. This paper presents questionnaires survey among staff in UiTM Puncak Alam about knowledge of Islamic vehicle financing. The findings indicate that the customers are aware about existence of Islamic vehicle product and they also selected Islamic vehicle product as their car financing. However, they are not really understands about the concept in Islamic vehicle financing in terms of the difference between Islamic and conventional banking. This study offers to the banking institutions to be more effective in term of giving understanding to the customer about the difference concept between Islamic and conventional product, where to avoid the misunderstanding between both products.